2017
DOI: 10.1371/journal.pone.0178700
|View full text |Cite
|
Sign up to set email alerts
|

Frameshift indels introduced by genome editing can lead to in-frame exon skipping

Abstract: The introduction of frameshift indels by genome editing has emerged as a powerful technique to study the functions of uncharacterized genes in cell lines and model organisms. Such mutations should lead to mRNA degradation owing to nonsense-mediated mRNA decay or the production of severely truncated proteins. Here, we show that frameshift indels engineered by genome editing can also lead to skipping of “multiple of three nucleotides” exons. Such splicing events result in in-frame mRNA that may encode fully or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 28 publications
5
71
0
Order By: Relevance
“…3D) [172]. Targeting of splice sites has also been shown to induce exon skipping within coding genes [173]. LncRNAs have many of the same regulatory elements as coding genes.…”
Section: Crispr/cas Technologymentioning
confidence: 99%
“…3D) [172]. Targeting of splice sites has also been shown to induce exon skipping within coding genes [173]. LncRNAs have many of the same regulatory elements as coding genes.…”
Section: Crispr/cas Technologymentioning
confidence: 99%
“…We evaluated predictive value of some other mRNA-level annotations, including propensity for exon skipping, distance to exon-intron junction, and fraction of transcript isoforms targeted. We hypothesized that exons that were multiples of 3 would be less functionally essential as compared to those that were not multiples of 3, since mutations could produce mRNA with intact reading frame [25]. It has been reported that exon skipping can be caused (besides alternative splicing) by both point mutations and by CRISPR-induced indels [26].…”
Section: Resultsmentioning
confidence: 99%
“…Given the recent insight that engineered mutations can be alternatively spliced and, hence, these genes can continue to produce transcripts that lack predicted changes to protein-coding capacity (Anderson et al, 2017;Lalonde et al, 2017;Mou et al, 2017), we tested whether the zebrafish mutant ryr alleles selected for this study were null mutations. We demonstrated that the 34C 'pan-RyR' antibody (Airey et al, 1990) was able to detect each of the three RyR channels expressed in the zebrafish myotome.…”
Section: Discussionmentioning
confidence: 99%
“…S1). As presumed null alleles can be expressed due to exon skipping (Anderson et al, 2017;Lalonde et al, 2017;Mou et al, 2017), we tested whether the mutant ryr alleles were truly protein null.…”
Section: Mutant Ryr Alleles Do Not Produce Protein Productsmentioning
confidence: 99%